Impact of sugarcane trash on fertilizer requirements for São Paulo, Brazil (Scientia Agricola, 2013)
The area under mechanized sugarcane (Saccharum spp.) harvesting is expanding in Brazil, increasing the return of trash to the soil. The main questions regarding this management are: (i) after adopting unburned mechanical harvesting, how long will it take to observe decreases in fertilizer requirements, (ii) what will be the magnitude of this decrease and, (iii) the impact in the short run of removing trash for energy purposes in the nutrient cycling? This study aimed to build an N prediction model for long term assessment of the contribution of sugarcane crop residues to sugarcane nutrition and to evaluate the cycling of other nutrients derived from crop residues. Keeping crop residues over the soil will increase soil N stock and N recovery by sugarcane, reaching equilibrium after 40 years with recovery of approximately 40 kg ha-1 year-1 of N. Removing trash for energy production will decrease the potential reduction in N fertilizer requirement. Of the total nutrients in the trash, 75 % of the K2O (81 kg ha-1 year-1) and 50 % of the N (31 kg ha-1 year-1) are in the tops, indicating the importance of maintaining tops in the soil to sustain soil fertility. Because the input data employed in the simulations are representative of the conditions in Southeast Brazil, these results might not be definitive for situations not represented in the experiments used in the study, but the model produced is useful to forecast changes that occur in the soil under different trash management.